(untitled) (Baghdad Science Journal, 2023)
Hepatocellular carcinoma (HCC) is the third most common cause of cancer-related death. Therefore, it is critical for researchers to understand molecular biology in greater depth. In several diseases including cancer, abnormal miRNA expression has been linked to apoptosis, proliferation, differentiation, and metastasis. Many miRNAs have been studied in relation to cancer, including miR-122, miR-223, and others. Hepatitis B and C viruses are the most important global risk factors for HCC. This study is intended to test whether serum miRNAs serve as a potential biomarker for both HCC and viral infections HBV and C. The expression of miRNA in 64 serum samples was analyzed by RT-qPCR. Compared to healthy volunteers, HCC patients’ sera expressed significantly lower levels of miR-122 and miR-223. Furthermore, we compared the expression of these miRNAs between early-diagnosed HCC patients and healthy controls. There was a significant difference between miR-122 expression in HCC sera and healthy volunteers’ sera (0.000 and 0.253, respectively), with a P value of <0.0001. Early diagnostic patients without treatment had completely deleted miR-122 expression levels, while those treated had slightly elevated levels. Clearly, miR-122 has been identified as a biomarker for early detection and follow-up of HCC treatment. HBV and HCV specimens expressed significantly lower levels of miRNA than normal samples with a P value of <0.0001. It is recommended that these findings be further investigated for diagnostic purposes. Further, these miRNAs are highly specific for diagnosing HCC, HBV, and HCV, making them valuable therapeutic indicators.